IL-6–174 G/C transversion might decrease male infertility risk: A case-control study - Tayyebeh Zamani-Badi; Mohammad Karimian; Javad Amini Mahabadi; Atieh Rafatmanesh; Hossein Nikzad (International Journal of Reproductive BioMedicine)
Background: Genetic predispositions have been identified as important factors in male infertility. Among the many genes related to male reproductive function, interleukin 6 (IL-6) has emerged as a key player. Despite the growing recognition of genetic factors in male infertility, the specific association between the IL-6–174 G/C genetic polymorphism and male infertility remains an area that needs further investigation. Objective: This investigation explores the correlation between the IL-6–174 G/C transversion and male infertility. Materials and Methods: In a case-control study, a total of 314 men who referred to the Kashan Infertility Center, Shahid Beheshti hospital, Kashan, Iran, were enrolled for IL-6–174 G/C polymorphism analysis. The study comprised 163 infertile participants as the case group and 151 fertile men as the control group. Following the screening, 2 ml of whole blood was collected from each participant. Cases were categorized into 3 subgroups based on World Health Organization criteria: (i) nonobstructive azoospermia (n = 42), (ii) oligozoospermia (n = 61), and (iii) asthenozoospermia (n = 60). After DNA extraction, genotypes of the samples at the -174 G/C (rs1800795) locus were determined using the polymerase chain reaction-restriction fragment length polymorphism method.